Buprenorphine Treatment Outcomes among Opioid‐Dependent Cocaine Users and Non‐Users. (25th June 2013) - Cunningham, Chinazo O.; Giovanniello, Angela; Kunins, Hillary V.; Roose, Robert J.; Fox, Aaron D.; Sohler, Nancy L.
<x xml:space="preserve">Abstract</x> Background and Objectives National treatment guidelines state that polysubstance users, including cocaine users, may not be appropriate candidates for office‐based buprenorphine treatment. However, data to support this recommendation are sparse and conflicting, and the implications of this recommendation may include limiting the usefulness of buprenorphine treatment, as cocaine use is common among opioid‐dependent individuals seeking buprenorphine treatment. We compared buprenorphine treatment outcomes (6‐month treatment retention and self‐reported opioid use over 6 months) in opioid‐dependent cocaine users versus non‐users who initiated buprenorphine treatment at an urban community health center. Methods We followed 87 participants over 6 months, collecting interview and medical record data. We used logistic regression models to test whether baseline cocaine use was associated with treatment retention and mixed effects nonlinear models to test whether baseline cocaine use was associated with self‐reported opioid use. Results At baseline, 39.1% reported cocaine use. In all participants, self‐reported opioid use decreased from 89.7% to 27.4% over 6 months, and 6‐month treatment retention was 54.5%. We found no significant difference in 6‐month treatment retention (AOR = 1.56, 95% CI: .58–4.17, p = .38) or self‐reported opioid use (AOR = .89, 95% CI: .26–3.07, p = .85) between cocaine users and non‐users. Conclusions and Scientific Significance This study demonstrates that buprenorphine treatment retention is not worse in cocaine users than non‐users, with clinically meaningful improvements in self‐reported opioid use. These findings suggest that opioid‐dependent cocaine users attain considerable benefits from office‐based buprenorphine treatment and argue for the inclusion of these patients in office‐based buprenorphine treatment programs. (Am J Addict 2013;22:352–357)